Biomechanics of the penalty stroke in roller hockey - Vaz, M. A. P.; Ramos, N.; Abrantes, J.; Queiros de Melo, F.; Conceicao, F. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
This paper describes a preliminary study on the biomechanics of the shot in roller hockey. This is a Portuguese sport having a most extensive prize list, where Portugal has been 15 times world champion, 20 European champions in senior male competition and won three world championships in senior female. Despite this impressive collection of titles, hockey continues to be the lesser studied sport, concretely regarding studies on biomechanics. The influence of sports equipment in the athlete's performance and a detailed analysis of the main technical gestures had not motivated yet the researchers for detailed studies to enable their optimization. The purpose of this study was to characterize the mechanical properties of the stick (Aleu) and its influence on the shot power.